Temperature-Swing Synthesis of Large-Size Single-Crystal LiNi0.6Mn0.2Co0.2O2 Cathode Materials. Issue 1 (29th January 2021) - Qian, Guannan; Li, Zhiyuan; Meng, Dechao; Liu, Jia-bing; He, Yu-Shi; Rao, Qunli; Liu, Yijin; Ma, Zi-Feng; Li, Linsen
Abstract : Single-crystal lithium-nickel-manganese-cobalt-oxide (SC-NMC) has recently emerged as a promising battery cathode material due to its outstanding cycle performance and mechanical stability over the tradional polycrystalline NMC. It is favorable to further increase the grain size of SC-NMC particles to achieve a higher volumetric energy density and minimize surface-related degradations. However, the preparation of large-size yet high performance SC-NMC particles faces a challenge in choosing a suitable temperature for sintering. High temperature promotes grain growth but induces cation mixing that negatively impacts the electrochemical performance. Here we report a temperature-swing sintering (TSS) strategy with two isothermal stages that fulfils the needs for grain growth and structural ordering sequentially. A high-temperature sintering is first used for a short period of time to increase grain size and then the reaction temperature is lowered and kept constant for a longer period of time to improve structural ordering and complete the lithiation process. SC-LiNi0.6 Mn0.2 Co0.2 O2 materials prepared via TSS exhibit large grain size (∼4 μ m), a low degree of cation mixing (∼0.9%), and outperform the control samples prepared by the conventional sintering method. This work highlights the importance of understanding the process-structure-property relationships and may guide the synthesis of other SC Ni-rich cathode materials.